Growth Improvement of a Marine Diatom Amphora subtropica BUUC1502 by Adding Phosphate and Silicate during the Cultivation - Nualkot, Supannee; Powtongsook, Sorawit; Kutako, Maliwan (Recent Science and Technology, 2024)
Nitrate, phosphate, and silicate are important nutrients in the culture medium for diatom cultivation. This study investigated the growth of a marine diatom Amphora subtropica BUUC1502 cultured with an addition of nutrients alongside the culture period. The first experiment was to evaluate the growth and nutrient consumption of the diatom when cultured in the standard F/2 medium at 30 PSU salinity. The results showed that a decrease in nitrate concentration was found but the total concentration was still sufficient for the diatom cultivation (>8 mg-N/L). On the other hand, phosphate and silicate were substantially decreased to almost zero within 5 days. The second experiment was to investigate the effect of an addition of nitrate and phosphate during cultivation on the growth of diatom by cultivation of diatom in 6 different treatments including 1) standard F/2 medium, 2) F/2 medium without phosphate (F/2-P), 3) F/2 medium without silicate (F/2-Si), 4) F/2 medium with phosphate addition alongside the culture (F/2+P), 5) F/2 medium with silicate addition alongside the culture (F/2+Si), and 6) F/2 medium with phosphate and silicate addition alongside the culture (F/2+P+Si). The nutrient addition was performed during days 2-13 and the nutrient concentration was increased between days 14-19 to compensate higher cells density. It was found that an addition of both phosphate and silicate alongside the cultivation could enhance the growth of the diatom with the highest density of 609.44x104 cells/ml whereas culturing with F/2 medium alone resulted in a maximum cell density of 318.33x104 cells/ml. However, an increment in nutrient addition during the final period (days 14-19) did not provide further growth of the diatom.